DIGITAL COMMUNICATION IN THE WORKPLACE: THE IMPACT OF TECHNOLOGY ON EMPLOYEE AND MANAGEMENT COMMUNICATION PATTERNS - Al-Amin; Indah Sulistiani (CV. Adiba Aisha Amira, 2025)
The development of digital communication technology has brought significant changes in communication patterns between employees and management in the world of work. This article explores the impact of technology on efficiency, the quality of interpersonal relationships, and employee well-being. Digital communication offers various advantages such as increased efficiency and ease of collaboration across geographies. However, challenges such as information overload, reduced depth of personal interactions, and privacy issues have also emerged as a consequence of the digitalisation of communication. To maximise the benefits and reduce the negative impacts, organisations need to develop balanced communication policies and provide adequate training to employees in the use of technology. With the right approach, digital communication technology can serve as a powerful tool to support productivity and well-being in the modern workplace.